Distinct Neurotoxicity Profile of Listeriolysin O from Listeria monocytogenes - Jana Maurer; Sabrina Hupp; Carolin Bischoff; Christina Foertsch; Timothy J. Mitchell; Trinad Chakraborty; Asparouh I. Iliev (Toxins, 2017)
Cholesterol-dependent cytolysins (CDCs) are protein toxins that originate from Gram-positive bacteria and contribute substantially to their pathogenicity. CDCs bind membrane cholesterol and build prepores and lytic pores. Some effects of the toxins are observed in non-lytic concentrations. Two pathogens, Streptococcus pneumoniae and Listeria monocytogenes, cause fatal bacterial meningitis, and both produce toxins of the CDC family—pneumolysin and listeriolysin O, respectively. It has been demonstrated that pneumolysin produces dendritic varicosities (dendrite swellings) and dendritic spine collapse in the mouse neocortex, followed by synaptic loss and astrocyte cell shape remodeling without elevated cell death. We utilized primary glial cultures and acute mouse brain slices to examine the neuropathological effects of listeriolysin O and to compare it to pneumolysin with identical hemolytic activity. In cultures, listeriolysin O permeabilized cells slower than pneumolysin did but still initiated non-lytic astrocytic cell shape changes, just as pneumolysin did. In an acute brain slice culture system, listeriolysin O produced dendritic varicosities in an NMDA-dependent manner but failed to cause dendritic spine collapse and cortical astrocyte reorganization. Thus, listeriolysin O demonstrated slower cell permeabilization and milder glial cell remodeling ability than did pneumolysin and lacked dendritic spine collapse capacity but exhibited equivalent dendritic pathology.